Ethnic Differences in the Frequency of CFTR Gene Mutations in Populations of the European and North Caucasian Part of the Russian Federation - Petrova, Nika; Balinova, Natalia; Marakhonov, Andrey; Vasilyeva, Tatyana; Kashirskaya, Nataliya; Galkina, Varvara; Ginter, Evgeniy; Kutsev, Sergey; Zinchenko, Rena (Frontiers in Genetics, 2021)
Cystic fibrosis (CF) is a common monogenic disease caused by pathogenic variants in the CFTR gene. The distribution and frequency of CFTR variants vary in different countries and ethnic groups. The spectrum of pathogenic variants of the CFTR gene was previously studied in more than 1500 CF patients from different regions of the European and North Caucasian region of Russia and the spectrum of the most frequent pathogenic variants of the CFTR gene and ethnic features of their distribution were determined. To assess the population frequency of CFTR gene mutations some of the common variants were analyzed in the samples of healthy unrelated individuals from the populations of the European part of the Russian Federation: 1,324 Russians from four European regions (Pskov, Tver, Rostov, and Kirov regions), representatives of five indigenous ethnic groups of the Volga-Ural region (Mari (n=505), Udmurts (n=613), Chuvash (n=780), Tatars (n=704), Bashkirs (n=517)), and six ethnic groups of the North Caucasus (Karachay (n=324), Nogai (n=118), Circassians (n=102), Abazins (n=128), Ossetians (n=310), Chechens (n=100)). The frequency of common CFTR mutations was established in studied ethnic groups. The frequency of F508del mutation in Russians was found to be 0.0056 on average, varying between four regions, from 0.0027 in the Pskov region to 0.0069 in the Rostov region. Three variants W1282X, 1677delTA, and F508del were identified in the samples from the North Caucasian populations: in Karachay, the frequency of W1282X mutation was 0.0092, 1677delTA mutation - 0.0032; W1282X mutation in the Nogai sample - 0.0127, the frequency of F508del mutations was 0.0098 and 1677delTA - 0.0098 in Circassians; in Abazins F508del (0.0039), W1282X (0.0039) and 1677delTA (0.0117) mutations were found. In the indigenous peoples of the Volga-Ural region, the maximum frequency of the F508del mutation was detected in the Tatar population (0.099), while this mutation was never detected in the Mari and Bashkir populations. The E92K variant was found in Chuvash and Tatar populations. Thus, interethnic differences in the spectra of CFTR gene variants were shown both in CF patients and in healthy population of the European and North Caucasian part of Russia.